2018
DOI: 10.22587/rjavs.2018.10.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Study of genetic polymorphism in BMPRIB gene and its association with improving twin production in Egyptian sheep and goats

Abstract: The present research was carried out to investigate the genetic polymorphism in BMPRIB (FecB) gene and to test whether this polymorphism is associated with improving twin production in Egyptian domestic sheep and goats. Blood samples were collected from 139 animals including 95 of sheep and 44 of goats. These animals involved 113 mothers (83 of sheep and 30 of goats) at the first, second, third and fourth parity. The other remaining 26 females (12 of sheep and 14 of goats) were at sexual maturity age to detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Moreover, the polymorphism of the BMPR1B gene has also been extensively studied in other species. Darwish (2018) found that BMPR1B polymorphism was significantly associated with litter size in Egyptian goats, which could significantly increase the rate of twin births. By constructing a vector with the mutant G allele of the A746G mutation, Zhao et al (2016) found that BMPR1B expression in pigs was 0.5-2 times higher in multiple tissue types of transgenic-positive F1 piglets than in their transgenic-negative siblings.…”
Section: Relationship Between Bmpr1b Mutation and Litter Size In Sheepmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, the polymorphism of the BMPR1B gene has also been extensively studied in other species. Darwish (2018) found that BMPR1B polymorphism was significantly associated with litter size in Egyptian goats, which could significantly increase the rate of twin births. By constructing a vector with the mutant G allele of the A746G mutation, Zhao et al (2016) found that BMPR1B expression in pigs was 0.5-2 times higher in multiple tissue types of transgenic-positive F1 piglets than in their transgenic-negative siblings.…”
Section: Relationship Between Bmpr1b Mutation and Litter Size In Sheepmentioning
confidence: 96%
“…The FecB mutation is widely distributed. In addition to Booroola Merino sheep, the mutation, which can improve twin production (El Seedy et al, 2017;Darwish, 2018), has been detected in Kendrapada sheep (Mahdavi et al, 2014) in India, Javanese sheep (Kumar et al, 2008) in Indonesia, Kalehkoohi sheep (Mahdavi et al, 2014) in Iran, and Hu sheep (Feng et al, 2006) in China. With deep research into high-fecundity genes in sheep, the FecB gene has been increasingly applied to the cultivation of new sheep varieties.…”
Section: Introductionmentioning
confidence: 99%